2011
DOI: 10.1002/dmrr.1177
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of FGF21 on glucose uptake in human skeletal muscle: implications for type 2 diabetes and obesity

Abstract: Plasma FGF21 is increased in T2D patients, and positively correlated with fasting insulin and BMI. However, FGF21 has direct effects in enhancing skeletal muscle glucose uptake, providing additional points of regulation that may contribute to the beneficial effects of FGF21 on glucose homeostasis. Whether increased plasma FGF21 in T2D is a compensatory mechanism to increase glucose metabolism remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 104 publications
8
144
2
1
Order By: Relevance
“…Among them, FGF21 was overexpressed in the liver of LPTEN KO mice, resulting in elevated plasma FGF21 levels. This insulin-sensitizing hepatokine is of particular interest since it is known to enhance glucose uptake in muscle [22,23] and to increase energy expenditure in WAT [30]. Interestingly, FGF21 was also reported to stimulate UCP1 expression and browning of WAT [24,25], in accordance with our data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among them, FGF21 was overexpressed in the liver of LPTEN KO mice, resulting in elevated plasma FGF21 levels. This insulin-sensitizing hepatokine is of particular interest since it is known to enhance glucose uptake in muscle [22,23] and to increase energy expenditure in WAT [30]. Interestingly, FGF21 was also reported to stimulate UCP1 expression and browning of WAT [24,25], in accordance with our data.…”
Section: Discussionsupporting
confidence: 90%
“…4C, the expression of several hepatokines and cytokines, previously reported to modulate muscle insulin sensitivity and/ or WAT homeostasis, was significantly affected in the liver of LPTEN KO mice. Of particular interest, was the fibroblast growth factor 21 (FGF21), which has a positive effect on muscle insulin sensitivity and browning of adipose tissue [22][23][24][25]. Expression of Fgf21 was also strongly upregulated in isolated primary hepatocytes of LPTEN KO mice and plasma FGF21 levels mirrored the liver mRNA expression, altogether supporting a major hepatic origin of circulating FGF21 levels ( Fig.…”
Section: Hepatic Pten Deletion Decreases Lipid Storage In Fat Depotsmentioning
confidence: 88%
“…Like Hojman et al, we did not find a correlation between insulin-stimulated FGF21 mRNA expression and insulin-stimulated FGF21 serum levels, suggesting that the FGF21, produced by muscle and fat, may play a different role than FGF21 produced by liver and may function as a paracrine or even an autocrine factor. In agreement with this hypothesis, Mashili et al (38) recently showed that FGF21 increases insulinstimulated glucose uptake in human myotubes. However, it is interesting to notice that PPARGC1 expression is downregulated in the skeletal muscles after 5 days of HF overfeeding as previously shown in these subjects (26), despite the known stimulatory effect of FGF21 on PPARGC1 and lipid oxidation in at least liver (3) and adipose tissue (39).…”
Section: Discussionmentioning
confidence: 54%
“…As summarised in Table 1, in vitro studies have shown that IL-6 increases myotube fatty acid oxidation and lipolysis via AMPK activation [32,33]. [46] No data available regarding endocrine metabolic effects of muscle-derived BDNF IL-6 ↑ GLUT4 translocation [19,20] ↑ Glucose uptake [15,19] ↑ Glycogen synthesis [18,20] ↑ Fatty acid oxidation [18][19][20] ↑ Lipolysis [32][33][34] Liver: ↑ Glucose production [23] Intestine: ↑ GLP-1 secretion of L cells [52] Pancreas: ↑ Beta cell proliferation [52] ↑ GLP-1 secretion of alpha cells [52] ↑ Proliferation and ↓ apoptosis of alpha cells [51] IL-13 ↑ Glucose uptake [28] ↑ Glucose oxidation [28] ↑ Glycogen synthesis [28] Liver: ↓ Glucose production [29] IL-15 ↑ Fatty acid oxidation [43] Adipose tissue: ↓ Lipid accumulation [44,45] ↑ Adiponectin secretion [44] Irisin No data available Adipose tissue: ↑ White to brown shift [98,111] No effect on browning [100] FGF21 ↑ Glucose uptake [99,136] Adipose tissue: ↑ White to brown shift [99] ↑ Glucose uptake [99] ↑ Adiponectin secretion [127,128] Liver: ↑ Fatty acid oxidation [137] ↑ Gluconeogenesis [137] Recently, a study using isolated mouse muscle reported that IL-6...…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%